2018
DOI: 10.1177/2050312118807626
|View full text |Cite
|
Sign up to set email alerts
|

Reference intervals for hematology test parameters from apparently healthy individuals in southwest Ethiopia

Abstract: Background:Clinical laboratory reference intervals are an important tool to identify abnormal laboratory test results. The generating of hematological parameters reference intervals for local population is very crucial to improve quality of health care, which otherwise may lead to unnecessary expenditure or denying care for the needy. There are no well-established reference intervals for hematological parameters in southwest Ethiopia.Objective:To generate hematological parameters reference intervals for appare… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
11
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(25 citation statements)
references
References 20 publications
2
11
1
Order By: Relevance
“…Significantly higher PLT count in females than males (310 vs 279 x10 9 /L) in our study is consistent with previous reports from Oman, Thailand, Zimbabwe and Mali [ 11 14 ]; and studies conducted in Ethiopia [ 19 , 20 , 26 ]. Females have lower total body iron storage but higher estrogen level, which favours stimulation of higher platelet production than males [ 25 ].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Significantly higher PLT count in females than males (310 vs 279 x10 9 /L) in our study is consistent with previous reports from Oman, Thailand, Zimbabwe and Mali [ 11 14 ]; and studies conducted in Ethiopia [ 19 , 20 , 26 ]. Females have lower total body iron storage but higher estrogen level, which favours stimulation of higher platelet production than males [ 25 ].…”
Section: Discussionsupporting
confidence: 93%
“…We also found higher median WBC count in females than males (6.8 vs 5.9x10 9 /L)which is consistent with a report from southern Taiwan [ 25 ]. On the other hand, the RI for WBC count is comparable with studies conducted in Ethiopia, like Debremarkos and Bahdar [ 19 , 22 ]; however, differences was noted in comparison to studies conducted in Southwest Ethiopia [ 20 ], The observed differences could be attributed to methodological differences to some extent although differences in prevalence of infections among the different populations cannot be ruled out. The current study, however, has used stringent exclusion criteria both at enrolment and during data analysis.…”
Section: Discussionsupporting
confidence: 65%
“…So far, most information about hematologic and biochemical RIs for pigs pertain to European and North American swine breeds [ 16 , 17 , 18 ]. The Clinical and Laboratory Standards Institute (CLSI) suggests that hematologic and biochemical RIs should be established for each geographical area and specific region’s population, since RIs may vary according to location, environment, breed, age, sex, nutrition, and test method [ 16 , 19 ]. It is possible that adopting hematologic and biochemical RIs from non-local data may lead to the misidentification of underlying diseases and the mismanagement of health conditions.…”
Section: Introductionmentioning
confidence: 99%
“…We ensured to follow the standard operating procedures for current experiment (Bimerew et al 2018). Hematological analysis was carried out using automatic hematology analyzer (XS-500i-Sysmex Europe GmBH) and were also compared with standard hematological parameters described in Schalm's Equine Hematology (Walton 2013).…”
Section: Hematological and Biochemical Parametersmentioning
confidence: 99%